Classic ciliated muconodular papillary tumor of the lung with a BRAF mutation - Minfen Zhang; Li Zhao; Shaoyan Liu; Xuexian Tan; Qingping Jiang; Na Wang (Elsevier, 2021)
Background: Ciliated muconodular papillary tumors (CMPTs) is a descriptive diagnostic term which indicates the composition of tumor cells (ciliated and mucous cells) and the pattern of growth (papillary). It is shown that the proportion of the various cells is different and the papillary structure is not necessary for diagnosis of this tumor. As a result, several scholars proposed that CMPT is a proximal-type bronchiolar adenoma (BA), a possibility which expanded the spectrum of CMPT. These morphological variations therefore introduced major challenges when diagnosing CMPTs. Case presentation: Multiple small nodules in both lungs were found in a 79-year-old female patient. A frozen section of the nodules was performed. Grossly, the nodules were jelly-like with clear boundaries and had a maximum diameter of approximately 4 mm. Microscopic examination showed glandular ducts, papillary, and even micropapillary structures. The cavities were lined by columnar and mucous cells. A conspicuous mucin pool was observed in low-power fields, in addition to floating tumor cells in the mucin pool. Based on these findings, atypical adenomatous hyperplasia of the lung was reported as the intraoperative rapid diagnosis, and the surgeon performed a lobectomy in the patient. A typical hematoxylin-eosin (HE) stain showed that the tumor consisted of three kinds of cells in different proportions, including ciliated columnar, mucous, and basal cells which were confirmed by CK5/6 and P63 immunohistochemistry staining. BRAF V600E protein was expressed in the tumor and at the same time the tumor was shown to harbor the BRAF gene mutation. Conclusion: We report a classic CMPT with a BRAF mutation that expressed BRAF protein. Classic lesions are easy to identify, whereas in cases of morphological variants the key to diagnosis of the disease is the diversity of cell components and the presence of basal cells.